The Influence of Business Scale and Financing on MSMEs Income in Malang City - Sholehuddin, Sulton; Arsiyanto, Tody (DINASTI RESEARCH, 2024)
Numerous obstacles are faced by micro, small, and medium-sized enterprises (MSMEs), one of the most important of which is restricted access to financial resources. The micro, small, and medium enterprises (MSMEs) in Malang City are the subject of this study project, which aims to explore the influence that financing and the size of the firm have on the income generated by these businesses. The information was analyzed via the use of descriptive statistics and regression analysis, and it was collected from a sample of one hundred micro, small, and medium-sized companies (MSMEs) that were of varying sizes and operating in a range of industries. According to the results of the research, there is a positive correlation between the income generated by micro, small, and medium-sized companies (MSMEs) and a range of sources of financing. These sources of funding include bank loans and government assistance programs. In addition to this, it was found that large-scale businesses have the potential to have a significant positive effect on the profitability of their operations.